2013
DOI: 10.1158/1940-6207.capr-13-0182
|View full text |Cite
|
Sign up to set email alerts
|

A Multiantigen Vaccine Targeting Neu, IGFBP-2, and IGF-IR Prevents Tumor Progression in Mice with Preinvasive Breast Disease

Abstract: A multi-antigen multi-peptide vaccine, targeting proteins expressed in pre-invasive breast lesions, can stimulate Type I CD4+ T-cells which have been shown to be deficient in both breast cancer patients and mice that develop mammary tumors. Transgenic mice (TgMMTV-neu) were immunized with a multi-antigen peptide vaccine specific for neu, IGFBP-2 and IGF-IR at a time when some of the animals already had pre-invasive lesions (18 weeks of age). While immunization with each individual antigen was partially effecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 37 publications
0
57
0
Order By: Relevance
“…Vaccination with this multiantigen, multipeptide vaccine inhibited the development of breast tumors in MMTV-neu transgenic mice genetically engineered to develop breast cancer and this efficacy was dramatically enhanced when combined with the retinoid X receptor agonist, bexarotene, but not when combined with the HER2 antagonist, lapatinib [75]. These investigators have also shown that DNA vaccination against several other self-proteins overexpressed during both early murine breast tumorigenesis and human DCIS inhibited the growth of MMTV-neu tumors [76].…”
Section: Autoimmune Mastitismentioning
confidence: 94%
“…Vaccination with this multiantigen, multipeptide vaccine inhibited the development of breast tumors in MMTV-neu transgenic mice genetically engineered to develop breast cancer and this efficacy was dramatically enhanced when combined with the retinoid X receptor agonist, bexarotene, but not when combined with the HER2 antagonist, lapatinib [75]. These investigators have also shown that DNA vaccination against several other self-proteins overexpressed during both early murine breast tumorigenesis and human DCIS inhibited the growth of MMTV-neu tumors [76].…”
Section: Autoimmune Mastitismentioning
confidence: 94%
“…Other promising approaches include the optimization of vaccine antigens to remove potential immune inhibitory epitopes and the use of multiple antigens to increase the breadth of the vaccine-elicited immune response (Cecil et al, 2014; Disis et al, 2013). Finally, the path forward for therapeutic cancer vaccines will depend on a more thorough understanding of the inhibitory signals in the TME and their application in combination with other immunomodulatory agents (van der Burg, Arens, Ossendorp, van Hall, & Melief, 2016).…”
Section: Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…Immunoprevention can produce an immunologic memory that calls upon a milieu of intrinsic cells and cytokines whenever a tumorigenic signal emerges. CaPR has been on the cutting edge of this exciting field in recent years and last year was no exception, including a preclinical vaccine study to prevent the progression of preinvasive lesions in a transgenic murine model of spontaneous basal-type breast cancer (20) and an early-phase clinical trial of a MUC1 vaccine in patients with advanced colorectal adenomas (21). CaPR also published provocative reviews this past year by prominent researchers in this field, e.g., Dhodapkar, who posited that both cancer cells and the immune system represent independent and complex systems with plasticity and adaptive potential and that the cross-talk may determine the evolution of both tumors and the host response (22) We also continue to publish important preclinical discoveries, including a novel combinatorial nanotechnologybased chemopreventive regimen to suppress neoplastic pancreatic lesions (24), studies of energy balance effects on Kras signaling in early pancreatic neoplasia (25,26), novel AMPK-independent preventive effects of metformin in lung tumorigenesis (27), and studies of social isolation, metabolic gene reprogramming and mammary tumors (28).…”
Section: Greetings Colleaguesmentioning
confidence: 99%